2019
DOI: 10.48550/arxiv.1912.03646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Universal Limitations on Quantum Key Distribution over a Network

Siddhartha Das,
Stefan Bäuml,
Marek Winczewski
et al.

Abstract: Entanglement is an intriguing quantum phenomenon with crucial implications for both fundamental physics and technological applications, e.g., quantum key distribution (QKD). In this paper, we show that multipartite private states from which secret keys are directly accessible to trusted partners are genuinely multipartite entangled states. With application to secure Quantum Internet, we consider the most general setup of multipartite quantum process (channel) in a network setting: multiplex quantum channel wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 110 publications
(254 reference statements)
0
24
1
Order By: Relevance
“…On practical side the point-to-point or relay-based QKD were achieved commercially and experimentally (see [Hor21] and references therein). From a theoretical perspective, the limitations in form of upper bounds on the key rate were developed in various device-dependent scenarios [CW04, HHHO09, TGW14, PLOB17, WTB17] (also see [AH09,DBWH19]).…”
mentioning
confidence: 99%
“…On practical side the point-to-point or relay-based QKD were achieved commercially and experimentally (see [Hor21] and references therein). From a theoretical perspective, the limitations in form of upper bounds on the key rate were developed in various device-dependent scenarios [CW04, HHHO09, TGW14, PLOB17, WTB17] (also see [AH09,DBWH19]).…”
mentioning
confidence: 99%
“…Indeed, if all parties share sufficient bipartite entanglement as to enable perfect teleportation any state of any given local dimension can be obtained from them and they are, therefore, universal resources in the standard paradigm of state manipulation under LOCC. Hence, from a more practical point of view, GME can be seen as a benchmark to produce multipartite quantum states useful for applications (possibly conditioned on further LOCC postprocessing) in the light of [16][17][18]. In fact, from this perspective our result uncovers the possibility in general to produce useful multipartite entanglement by mixing partially separable states, as the work of [20] exemplifies in a particular case in the context of quantum cryptography.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, most relevant states for applications-like graph states-are GME and the set of biseparable states is closed under LOCC; thus, this classification is welldefined within the standard paradigm of state manipulation under LOCC and biseparable states are then fundamentally limited for many applications. Actually, it has been shown that GME is in general necessary to achieve maximum sensitivity in quantum metrology [16,17] and to establish a multipartite secret key [18]. Nevertheless, all these considerations only involve the single-copy regime.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a majority of prepare-and-measure protocols [20][21][22][23][24][25][26] is vulnerable to the Trojan horse attacks [27,28]. Furthermore, in particular, all proposed QSS protocols will confront the linear rate-distance limitation [29][30][31]. This limitation constricts the key rate and transmission distance of QSS.…”
Section: Introductionmentioning
confidence: 99%